RANCANG BANGUN APLIKASI SISTEM PELAYANAN MASYARAKAT BERBASIS WEB PADA KECAMATAN CADASARI KABUPATEN PANDEGLANG - Gabriel Ryfan Kenny (2020)
The regional governments have the responsibility to serve and interact with the locals. Unfortunately, most of the local regional governments fail to offer their service to the local community. The main reason of this is that the local regional governments do not have enough infrastructure, especially in the information technology sector. They're unable to provide a media for data and information exchange. For example, the locals have to visit the regional office to get their certificate service. So, this study and research intend to improve the information technology of the citizen service by building a web based citizen service which will be implemented at the local sub-district to help the office to improve their services. In this research the writer uses observation and interview data collection methods. The system analysis method used by the writer is the PIECES method. The software development method used by the writer is the waterfall model. The main reason of this is, the waterfall model is suitable and fits to design a large scaled system. The result of this research is a web based citizen service system which intends to help the sub-district office to improve their ability to share information to their citizens and help the office's manpower.